2023
DOI: 10.1177/17562848231190976
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of vonoprazan–amoxicillin dual therapy for Helicobacter pylori first-line treatment: a single-center, randomized, controlled trial

Xiaolei Wang,
Guigen Teng,
Xinhong Dong
et al.

Abstract: Background: With the increase in antibiotic resistance, the success rate of Helicobacter pylori ( H. pylori) eradication therapy has declined in recent years. Vonoprazan–amoxicillin (VA) dual therapy has been reported to be a promising regimen. Objectives: To compare the efficacy and safety of VA dual therapy and bismuth quadruple therapy containing amoxicillin and clarithromycin for H. pylori first-line eradication, and to further analyze the effects of clarithromycin resistance on eradication rate. Design: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…However, in China, the same therapy has resulted in a very low eradication rate, falling below 80%. The efficacy was improved (>90%) when the treatment duration was extended to 14 days 25–30 . It should be note that all the VA groups were treated with VPZ 20 mg bid and we found that high dose and low dose amoxicillin does not contribute significant difference to the cure rate.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…However, in China, the same therapy has resulted in a very low eradication rate, falling below 80%. The efficacy was improved (>90%) when the treatment duration was extended to 14 days 25–30 . It should be note that all the VA groups were treated with VPZ 20 mg bid and we found that high dose and low dose amoxicillin does not contribute significant difference to the cure rate.…”
Section: Discussionmentioning
confidence: 57%
“…The efficacy was improved (>90%) when the treatment duration was extended to 14 days. [25][26][27][28][29][30] It should be note that all the VA groups were treated with VPZ 20 mg bid and we found that high dose and low dose amoxicillin does not contribute significant difference to the cure rate. Possibly, a universally effective regimen will emerge, but it will likely require higher doses of VPZ such as 30 or 40 mg bid or tid in some regions.…”
Section: F I G U R Ementioning
confidence: 56%
See 3 more Smart Citations